1997
DOI: 10.1046/j.1365-2036.1997.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of severe ulcerative colitis

Abstract: Severe ulcerative colitis is a potentially life‐threatening condition but the mortality has fallen dramatically over the past 30–40 years. It is now less than 2%, including surgical mortality, and should only be seen in patients with significant co‐existing disease. Early recognition of the severity of the colitis, intensive medical therapy, close liaison between physician and surgeon, and prompt surgery when necessary have all contributed to this improved outcome. Despite the use of high‐dose intravenous cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…7 Indeed, many clinicians may continue medical therapy for 10 days or more in patients in whom there is some evidence of continued improvement. 24 The present study showed that patients with an AI value in excess of 200 after 2 weeks of medical therapy had a high chance of undergoing colectomy. This cutoff value also seemed to be valid for both sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 92%
“…7 Indeed, many clinicians may continue medical therapy for 10 days or more in patients in whom there is some evidence of continued improvement. 24 The present study showed that patients with an AI value in excess of 200 after 2 weeks of medical therapy had a high chance of undergoing colectomy. This cutoff value also seemed to be valid for both sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 92%
“…The cumulative colectomy rate among patients with UC has been reported at 8 to 20 percent and 11 to 28 percent at five and ten years after onset, respectively. [3][4][5][6] Recently, proctocolectomy and reconstruction with an ileal pouch-anal anastomosis has become the leading surgical procedure for patients with UC and has provided both acceptable function and quality of life. 7,8 However, there are many complications associated with this surgical procedure, such as pelvic sepsis, high stool frequency, fecal incontinence, evacuation disorders, and pouch failure.…”
mentioning
confidence: 99%
“…Early recognition of prognostic factors, intensive medical therapy, and early surgery for non-responders have all contributed to improved outcome. 2 In spite of the use of intensive intravenous glucocorticoid treatment (IIVT), approximately 20-30% of patients fail to respond and will require surgery. The short term colectomy rate has remained stable during the last 30 years 3 ; moreover, approximately one third of patients who escape early colectomy will require surgery in the long term, for a further severe attack or for frequent relapsing disease.…”
Section: Introductionmentioning
confidence: 99%